2021
DOI: 10.1002/adfm.202105348
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Lamellar Chitosan Scaffold for Soft Gingival Tissue Regeneration

Abstract: Mucogingival surgery has become a common procedure for soft gingival tissue reparation in dental clinical practice, which mainly relies on autograft or commercial collagen membranes (CM). However, the autograft faces grand challenges in source availability and long‐term post‐surgery pain management, and the CM is restricted by its poor mechanical properties in an aqueous environment. Here, it is reported that a bio‐inspired lamellar chitosan scaffold (LCS) with long range ordered porous structure, manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 62 publications
(40 reference statements)
0
23
0
Order By: Relevance
“…The directional freeze-casting is a promising technique used to fabricate various kinds of TE scaffolds with oriented pores by introducing directional temperature gradients in the slurry. [23,33,34] The pore size can be modulated via varying the temperature of the freezing mold or the cooling rates of the slurry. [35,36] Herein, in order to fabricate a radially oriented porous scaffold, a precooling thick-walled (10 mm thick) tubular steel mold was used with its inner wall as the freezing surface to introduce a radially oriented temperature gradient in the slurry (Figure 2A).…”
Section: Preparation and Characterization Of Cs/ha Nanocomposite Scaf...mentioning
confidence: 99%
See 1 more Smart Citation
“…The directional freeze-casting is a promising technique used to fabricate various kinds of TE scaffolds with oriented pores by introducing directional temperature gradients in the slurry. [23,33,34] The pore size can be modulated via varying the temperature of the freezing mold or the cooling rates of the slurry. [35,36] Herein, in order to fabricate a radially oriented porous scaffold, a precooling thick-walled (10 mm thick) tubular steel mold was used with its inner wall as the freezing surface to introduce a radially oriented temperature gradient in the slurry (Figure 2A).…”
Section: Preparation and Characterization Of Cs/ha Nanocomposite Scaf...mentioning
confidence: 99%
“…[17] Previous studies have certified that scaffolds with oriented porous structure are more favorable for infiltration and migration of surrounding cells, exchange of nutrients and wastes, and also deposition of extracellular matrix, compared with scaffolds with random porous structure. [18][19][20] Among a variety of methods, [2,3] the burgeoning 3D printing [21,22] and directional freeze-casting techniques [23,24] are the most powerful approaches to engineer TE scaffolds with oriented porous structure, which both have their own advantages. 3D printing, for example, can spatially control the structure and composition of scaffolds to an unprecedented degree.…”
Section: Introductionmentioning
confidence: 99%
“…The suture sheath exhibits low friction and tissue-like stiffness without compromising mechanical properties. Inspired by the hierarchical arrangement of collagen fibers, Mredha et al [40] developed The gingiva LCS (-) Induce macrophage differentiation to M2 macrophages Tissue regeneration [28] Animal: tree frogs Structured hydrogel adhesive (-)…”
Section: Mimicking Human Tissue In Bioinspired Hydrogelsmentioning
confidence: 99%
“…The lamina propria of the gingival is a tangle of connective tissue fibers, the most important component of which is collagen fibers, about 56%. Inspired by the natural lamellar structure of gingiva, Feng et al [28] prepared porous lamellar chitosan scaffold (LCS) (shown in Figure 1C) via the bidirectional freezing method. The LCS not only shows shape memory function in the hydrated state but also promotes cell proliferation and vessel formation.…”
Section: Mimicking Human Tissue In Bioinspired Hydrogelsmentioning
confidence: 99%
“…Chitosan, a cationic polysaccharide composed of β-(1–4) linked 2-acetamido-2-deoxy-β- d -glucopyranose and 2-amino-2-deoxy-β- d -glycopyranose, is an alkaline deacetylation product of chitin, the second most abundant polysaccharide, which mainly comes from the exoskeletons of crustaceans, insects, beetles, as well as the cell walls of fungi [ 1 ]. Many of the applications of chitosan in several fields are based on its biological and excellent cationic properties [ 2 , 3 ], including biocompatibility [ 4 ], low immunogenicity, low or no toxicity, and antibacterial and moisture retentive properties [ 5 , 6 ]. Chitosan-based nanomaterials (such as nanogels, nanofibers, and nanocrystals) have been paid increasing attention due to their size-specific and free amine properties.…”
Section: Introductionmentioning
confidence: 99%